Sterilization method of contaminated oil palm plantlets affects the survival rate during acclimatization - Masna Maya Sinta; Lailia Zubaidah; Rizka Tamania Saptari; Imron Riyadi; Galuh Wening Permatasari; Riza Arief Putranto; Annisa A Aksa; Larasati D Mahardhika; Yuli Setiawati; Hayati Minarsih; Ernayunita Ernayunita (Menara Perkebunan, 2023)
Contamination in the in vitro culture is a critical problem causing the failure of seed production. Contamination in the oil palm plantlet is detrimental, considering that oil palm propagation is difficult and takes a long time. This research aimed to study the effect of sterilization during acclimatization of the contaminated oil palm plantlets by fungi on viability and to determine the optimum viability achieved from the contaminated materials. The materials used were contaminated plantlets of oil palm with roots, four leaves, and a height of about 17 cm. The plantlets were removed from the tube and cleaned with running tap water, then were sterilized, with treatments P1: soaking in benomyl-mancozeb-sodium hypochlorite and mannitol and rinsing with aquadest, P2: soaking in benomyl-mancozeb, P3: soaking in mancozeb. Cleaning plantlets under running tap water was carried out as a control treatment. The results showed that at 10 weeks after acclimatization, the survival rate of plantlets in each treatment (P1, P2, and P3) was significantly higher than that of the control. Sterilization methods affect the time new leaves emerge, leaf condition after sterilization treatment, and shoot height. The lowest fungal contamination after treatments was found in P2, followed by P3. After 3 months, plantlet survival rate decreased, with the highest survival rate in treatment P3 (32.3%) followed by treatment P2 (22.5%). In conclusion, acclimatization of contaminated oil palm plantlets can be carried out using a suitable sterilization treatment. Sterilization affects the survival rate and growth of in vitro-contaminated oil palm plantlets during acclimatization.